2021
DOI: 10.1183/13993003.00880-2021
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-C/VEGFR-3 signalling in macrophages ameliorates acute lung injury

Abstract: BackgroundSuccessful recovery from acute lung injury requires inhibition of neutrophil influx and clearance of apoptotic neutrophils. However, the mechanisms underlying recovery remain unclear. We investigated the ameliorative effects of vascular endothelial growth factor (VEGF)-C/VEGF receptor 3 (VEGFR-3) signalling in macrophages in lipopolysaccharide (LPS)-induced lung injury.MethodsLPS was intranasally injected into wild-type and transgenic mice. Gain and loss of VEGF-C/VEGFR-3 signalling function experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 38 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…Vascular endothelial growth factor A (VEGF-A) signaling plays critical roles in increasing vascular permeability; however Spry4 has been shown to negatively regulate VEGF-A pathway [ 44 , 45 ]. The protective effects of macrophage Spry4 deficiency against sepsis-induced ALI might be associated with the induction of VEGF-C pathway [ 46 ]. In addition, Spry4 silence facilitated the migration and adhesion of endothelial and epithelial cells that may also enhancing the reparative function of the lung during sepsis [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial growth factor A (VEGF-A) signaling plays critical roles in increasing vascular permeability; however Spry4 has been shown to negatively regulate VEGF-A pathway [ 44 , 45 ]. The protective effects of macrophage Spry4 deficiency against sepsis-induced ALI might be associated with the induction of VEGF-C pathway [ 46 ]. In addition, Spry4 silence facilitated the migration and adhesion of endothelial and epithelial cells that may also enhancing the reparative function of the lung during sepsis [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, while scRNA‐sequencing data showed that the Flt4 expression level was minuscule in chondrocytes from mice with PTOA and patients with OA (Supplementary Figure 10, available on the Arthritis & Rheumatology website at https://doi.org/10.1002/art.42441), evidence of VEGFR‐3 expression was previously reported in the articular cartilage from OA patients who had undergone knee replacement and in the cartilage–subchondral bone interface (40,41). In addition, VEGF‐C can affect osteoclasts (42) and macrophages (43) via its interaction with VEGFR‐3. Thus, VEGF‐C may exert effects directly on articular cartilage, bone tissue, or immune cells in addition to the SLS, which requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been shown that the uptake of apoptotic cells by murine alveolar macrophages and human monocyte-derived macrophages is inhibited by Vegf depletion, while Vegf overexpression significantly enhances apoptotic cell uptake by alveolar macrophages in vivo, indicating a positive regulatory role for Vegf in macrophage endocytosis and clearance of apoptotic cells [44]. Furthermore, Vegf-C/Vegfr-3 signaling increases the macrophage efferocytosis of apoptotic neutrophils via the upregulation of macrophage integrin αv [63], further indicating a role for Vegf in regulating macrophage phagocytosis.…”
Section: Discussionmentioning
confidence: 99%